Implementation of 5G Standalone Private Network for UHD Video Streaming - Adriansyah, Ahmad; Soim, Sopian; Aryanti (Universitas Muhammadiyah Surakarta, 2025)
The growing user preference for Ultra High Definition (UHD) video content on various Over-the-Top (OTT) platforms presents a significant challenge in Indonesia, where 5G network coverage is limited and primarily based on the Non-Standalone (NSA) architecture. This study demonstrates the development and implementation of an affordable private 5G Standalone (SA) network as a viable alternative for high-quality video streaming. A private 5G SA network was constructed using open-source Open5GS software and a Universal Software Radio Peripheral (USRP) B210. Its performance was evaluated through speed tests and traffic sniffing analysis during 4K and 8K video streaming and then compared against a public 5G NSA network in Palembang. The results showed that the private SA network delivered significantly faster upload speeds and more consistent low latency than its public NSA counterpart. Although some public NSA locations provided higher download speeds, both network configurations achieved flawless data transmission with zero packet loss and high throughput during UHD streaming. The study concludes that a private 5G SA network is a highly effective, flexible, and slightly superior alternative for deployment, capable of reliably supporting the demands of UHD video streaming.